Optoelectronic figure of merit of a metal nanoparticle—quantum dot (MNP-QD) hybrid molecule for assessing its suitability for sensing applications. (11th January 2018) - Hapuarachchi, Harini; Mallawaarachchi, Sudaraka; Hattori, Haroldo T; Zhu, Weiren; Premaratne, Malin
Abstract: Recently, many have studied various configurations of metal nanoparticle-quantum dot (MNP-QD) hybrid molecules based on different metals and tunable parameters. In this paper, we aim to incite the interest in using MNP-QD nanohybrids, which possess sensing capabilities superior to those of the individual constituents, for sensing applications that rely on scattered light. When assessing whether a given MNP-QD configuration is suited for an application, sometimes it is hard to assess the pros and cons of a given configuration against other candidates. Here we propose a simple, elegant relative figure of merit (RFoM), which focuses on maximizing the scattered intensity and the refractive index sensitivity of the nanohybrid, to rank the suitability of viable MNP-QD configurations for a particular sensing application. We use the proposed RFoM to analyse the optical spectra of noble, transition, post transition and alkali metal based MNP-QD nanohybrids using the representative metals Au, Ag, Cu, Al and Na, adopting a generalized nonlocal optical response (GNOR) method based cavity QED approach. Based on our observations, we suggest how the usage of MNP-QD nanohybrids could improve the conventionally studied tumour targeting applications. Moreover, we propose potential substitutes for noble metals conventionally considered for MNP-QD nanohybrids.